A Chinese patient with developmental and epileptic encephalopathies (DEE) carrying a TRPM3 gene mutation: a paediatric case report - Kang, Qingyun (BMC Pediatr, 2021)
BACKGROUND: Developmental and epileptic encephalopathies (DEEs) are a heterogeneous group of chronic encephalopathies characterized by epilepsy with comorbid intellectual disability that are frequently associated with de novo nonsynonymous coding variants in ion channels, cell-surface receptors, and other neuronally expressed genes. Mutations in TRPM3 were identified as the cause of DEE. We report a novel patient with DEE carrying a de novo missense mutation in TRPM3, p.(S1202T); this missense mutation has never been reported. CASE PRESENTATION: A 7-year and 2-month-old Chinese patient who had recurrent polymorphic seizures was clinically diagnosed with DEE. A de novo missense mutation in TRPM3, which has not yet been reported, was identified in this case. The patient had a clinical phenotype consistent with previous reports. CONCLUSIONS: These findings could expand the spectrum of TRPM3 mutations and might also support that de novo substitutions of TRPM3 are a cause of DEE.